Model Pertumbuhan Populasi untuk Pengendalian Populasi Akasia Berduri (Acacia nilotica (L.) Willd. Ex Del.) di Taman Nasional Baluran - Supriyadi Supriyadi (Universitas Atma Jaya Yogyakarta, 2007)
The savannas in Baluran National Park have been severely invaded by Acacia nilotica. The invasion reduced grazing areas and created wildlife watching problems for tourists. Therefore, population control management should be developed. The aim of the study was to construct a population growth model in relation to the control of the population in the park. The model was an age structured one which consisted of seed class, age class <1 year, age class 1-<2 years, age class 2-<3 years, age class 3-<4 years, and age class 4 years. It was assumed that a temporary seed bank exists; there is no seed dormancy; seeds are produced by age class 4 years; and the number of seedlings is determined by available space. The population size was expressed as the number of individuals per hectare. The population control scenario included effects of complete elimination and partial elimination in the first year. Each of those was combined with seed harvesting. The total population growth pattern generated by the model was similar to the logistic one but with a bit oscillation before a stable population size was reached. More important parameters in the model were germination rate, seedling survival rate, number of seeds per individuals, maximum population size, and survival rate of age class 4. The simulation results showed that control measures of the population were effective when seed harvesting was carried out. A periodic partial elimination combined with seed harvesting might be useful. Seed harvesting should be applied every year to retard the growth and to prevent the spread of A. nilotica populations in the savannas.